EKSTRAKSI ANDROGRAFOLID DARI Andrographis paniculata (Burm.f.) Nees MENGGUNAKAN EKSTRAKTOR SOXHLET - Ichwan Ridwan Rais (Pharmaciana, 2014)
Chemical component extraction from plant herbal influenced by various aspect, such asextraction technique or chemical component character from the plant. Extraction method and solventpolarity exteremly influence chemical component transfer from the cell of plant to solvent solution.Soxhlet is extraction system instrument with frequently same solvent extraction based on liquid-steamcirculation process of the solvent. Solvent polarity to extract chemical component of the plant herbaldepend on chemical component character it self and ability to penetrate cell membrane.Andrographolide, an active chemical component of Andrographis paniculata has been suggested themost active constituent that responsible to activity of Andrographis paniculata in herbal medication.This chemical constituen has solubility character in solvent with middle polarity that indicates solventelection to extract it. This study shows that chemical component extraction of herbal plant influencedby solvent polarity. Thin Layer Chromatography qualitative analyses indicate that absolute polar andAndrographis paniculatanonpolar solvent could not extract andrographolide, different from middle polarity. Andrographolideextraction with similar solvent and correct method offer extract yield with 16,6% andrographolide.